2008
DOI: 10.1007/s11575-008-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

FDI Ownership Strategy: A Japanese-US MNE Comparison

Abstract: and Key Results 0Much of the extant literature characterizes international joint venture (IJV) as a less stable and less successful form of organization. In this view, the IJV is considered a suboptimal ownership strategy, one where the firm lacks control over its operations, compared to wholly-owned subsidiary (WOS). 0 We tested this widespread view on IJV and WOS by analyzing a large, longitudinal sample of Japanese MNEs, comparing our results to those from US MNEs reported in Desai et al. (2004a) and Gomes-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 64 publications
1
17
1
Order By: Relevance
“…We observe divergent degrees of control, ranging from minority, via 50‐50 to majority ownership configurations, each representing divergent entry scenarios and possibilities at the time of market entry. This corresponds with earlier findings that highlight the propensity of Japanese MNEs to opt for JV configurations when entering emerging markets (Delios & Beamish, ; Jung, Beamish, & Goerzen, ). Apart from the institutional possibilities, ownership involves balancing control and commitment.…”
Section: Discussionsupporting
confidence: 91%
“…We observe divergent degrees of control, ranging from minority, via 50‐50 to majority ownership configurations, each representing divergent entry scenarios and possibilities at the time of market entry. This corresponds with earlier findings that highlight the propensity of Japanese MNEs to opt for JV configurations when entering emerging markets (Delios & Beamish, ; Jung, Beamish, & Goerzen, ). Apart from the institutional possibilities, ownership involves balancing control and commitment.…”
Section: Discussionsupporting
confidence: 91%
“…Although the studies identified have not recognized explicitly the intensity dimension developed above, some researchers have operationalized international experience in a manner consistent with our conceptualization of the intensity dimension. Some researchers have operationalized international experience as the number of subsidiaries established in the host country (Jung et al . 2008), region (Barkema and Drogendijk 2007) or internationally (Fey et al .…”
Section: International Experience As a Multidimensional Constructmentioning
confidence: 99%
“…Some past studies analyzed the choice between greenfield investment and acquisition entry strategy by the investing foreign MNEs (e.g., Arslan & Larimo, 2011;Brouthers & Brouthers, 2000;Datta, Herrmann, & Rasheed, 2002;Demirbag et al, 2008Demirbag et al, , 2009Hennart & Park, 1993;Larimo, 2003;Shimizu, Hitt, Vaidyanath, & Pisano, 2004;Slangen & Hennart, 2008). Other IB studies addressed the ownership mode strategy of MNEs by studying the choice between wholly owned subsidiary or joint venture formation (e.g., Anderson & Gatignon, 1986;Arslan & Larimo, 2010;Brouthers & Hennart, 2007;Jung, Beamish, & Goerzen, 2008;Luo, 2001). However, the literature review reveals that very few IB and market entry studies (e.g., Jakobsen & Meyer, 2008) have analyzed acquisition entry strategy of MNEs specifically by differentiating between full acquisitions versus partial acquisitions, in case the MNE decides to acquire a local firm at time of market entry in a new target country.…”
Section: Introductionmentioning
confidence: 99%